Study of the Kinematics and Dynamics of the Ring Pack of a Diesel Engine by Means of the Construction of CFD Model in Conjunction with Mathematical Models (2021)
The present research aims to analyze the kinematic and dynamic behavior of the piston ring package. The development of the research was carried out through the development of numerical simulation by means of CFD. The analysis involves the three piston rings for the development of simulations that are closer to the real conditions of the engine since most of the investigations tend to focus on the study of the compression ring only. The simulation was reinforced by the incorporation of mathematical models, which allow determining the piston kinematics, the lubrication properties as a function of temperature, contact friction, and gas leakage. For the simulation, the CAD of the piston and the connecting rod—crankshaft mechanism was carried out, taking as a reference the geometry of a diesel engine. From the results obtained, it was possible to show that the first ring exhibits considerably greater radial and axial movement compared to the second and third piston rings. Additionally, it was shown that the first and second rings tend to maintain a negative tilt angle throughout the combustion cycle, which facilitates the advancement of the combustion gases over the piston grooves. Therefore, it is necessary to use strategies so that these rings tend to maintain a positive inclination. The analysis of the pressure conditions in the second ring are 150% and 480% higher compared to the conditions present in the third ring. Due to the above, it is necessary to focus efforts on the design of the profile of this ring. The study of energy losses showed that the combination of leakage gases and friction are responsible for a mechanical loss between 6–16%. In general, the development of the proposed methodology is a novel tool for the joint analysis of the kinematic characteristics, pressure conditions, and energy losses. In this way, integrated analysis of changes caused by piston ring designs is possible.